2019
DOI: 10.1371/journal.pone.0225254
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the capacity of Malawi’s district and central hospitals to manage traumatic diaphyseal femoral fractures in adults

Abstract: BackgroundThe burden of musculoskeletal trauma is growing worldwide, disproportionately affecting low-income countries like Malawi. However, resources required to manage musculoskeletal trauma remain inadequate. A detailed understanding of the current capacity of Malawian public hospitals to manage musculoskeletal trauma is unknown and necessary for effective trauma system development planning.MethodsWe developed a list of infrastructure, manpower, and material resources used during treatment of adult femoral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 38 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…A study done in Zambia demonstrated that only 16.5% of the hospitals met the WHO minimum standards of safe surgical care [20]. There is a similar situation in Malawi with low standards of safe surgery in rural health facilities [21]. In addition, the need of improvement in global surgical care, particularly in low-income and middle-income countries is described in a review from 2019 [21].…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Zambia demonstrated that only 16.5% of the hospitals met the WHO minimum standards of safe surgical care [20]. There is a similar situation in Malawi with low standards of safe surgery in rural health facilities [21]. In addition, the need of improvement in global surgical care, particularly in low-income and middle-income countries is described in a review from 2019 [21].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, central hospitals face challenges in providing even skeletal traction due to broken drills, limited traction pins, and inadequate traction frames and weights. 28 Improving hospital infrastructure, bolstering surgical staff, and improving availability of material resources would all likely improve the patient experience navigating the Malawian health system. However, many of the patients' frustrations could be addressed by fostering a culture of quality improvement that is accountable to patients -a culture where patients' experiences and outcomes are noted, acknowledged, and addressed.…”
Section: Discussionmentioning
confidence: 99%
“…27 No public hospital nationwide has the minimum required resources to adequately treat FSF. 28 The public hospital system in Malawi has three tiers: rural health centers, providing basic medical and maternity care only; district hospitals, staffed by general doctors and clinical o cers (non-physician clinicians); and central hospitals staffed by specialists including surgeons. Operative treatment of FSFsthe international gold standard 29 -is performed only in central hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted in all four central hospitals in Malawi. Central hospitals in Malawi are tertiary level institutions which provide specialist care (32).The study was conducted in the central hospitals because they serve as referral centres for all other facilities in all the three regions of Malawi (i.e. northern, central and southern regions).…”
Section: Study Settingmentioning
confidence: 99%